Analysis for tensile strength of multi-phase alloy composed of ductile matrix and brittle reinforcement with circumferential notch in As-cast AZX912 Mg alloy. (October 2022) - Higuchi, Yu-ki; Ishina, Toshiyuki; Hamada, Shigeru; Matsumoto, Toshiharu; Noguchi, Hiroshi
Highlights: Tensile test of an as-cast AZX912 Mg Alloy with a circumferential notch. Step I: cracking of the transversely long reinforcing phase that exists ahead of the defect. Step II: fracture of the matrix ligament between the cracked reinforcing phase and the defect. DIC observation of tensile tests conducted on AZ31 and equivalent plastic strain by FEM. Step I is dominant. Abstract: Non-combustible Mg alloys have been developed, and they tend to form cast defects. A crack propagates stably from a defect before the final fracture. The stable crack propagation is divided into two steps. I: cracking of the transversely long reinforcing phase that exists ahead of the defect, and II: fracture of the matrix ligament between the cracked reinforcing phase and the defect. In this study, a tensile test of an as-cast AZX912 Mg Alloy with a circumferential notch is performed. The equivalent plastic strain in the ligament is determined by FEM analysis based on the actual crack observed during stable propagation. On the other hand, the maximum equivalent strain tolerated by the ligament is obtained from the DIC observation of tensile tests conducted on AZ31 whose fracture elongation is about 0.15. As a result of comparing the equivalent plastic strain on the ligament with the equivalent strain that the ligament can tolerate, the latter is smaller than the former. Therefore, it can be assumed that the second step occurs immediately after Step I. The authors conclude that Step I should be the focus of attention.